Pemetaan Sebaran Air Tanah Asin Pada Aquifer Dalam di Wilayah Semarang Bawah - M. Irham Nurwidyanto; Sugeng Widodo; Refyana T. Achmad (BERKALA FISIKA, 2012)
A research to mapping of saline groundwater spreading at deep aquifer in SEMARANG Awash  area, exactly at 49 zone, coordinate X(422000-445000), Y(9222100-9232000) is carry out. Electrical conductivity used in this research as approximation to saline value of groundwater. Then, the isoconductivity contour map made based on that’s conductivity value using surfer 7 to see the mapping of saline groundwater spreading. After that, a hydrochemistry analyze method resemble to Trilinier Piper diagram and Chlorida-Carbonat Ratio (R) used to analyze caused factor of saline from groundwater. Base on the groundwater saline grade clasification from PAHIAA, Jakarta, the groundwater at deep aquifer of Semarang bawah area come in insipid that spread out almost in all Semarang bawah area and insipid-saltish groundwater clasification that just found in two area, are central Pedurungan (Tlogosari) and Tugu Muda direct to Pemuda street area. Base on Trilinier Piper diagram and Chlorida-Carbonat Ratio (R) analyze,  the saline of groundwater at deep aquifer in  Semarang Awash area is the effect from the sea water intrusio, except in central Semarang area the salted of groundwater it’s not caused by the sea water intrution, may be couse by dilution of salt mineral which imbedded in the groundwater..